Intervening on behalf of the human right to health: who, when, and how? - Muyskens, Kathryn (Human rights review, 2021)
A common understanding of the political function of human rights is as a trigger for international intervention, with states typically understood to be duty bound by these rights claims. The unique character of the human right to health raises some complications for these conventional views. In this paper, I will argue that because of the unique character of the human right to health, intervention on its behalf can be justified not only in response to outright violation, but also due to unmet needs of populations. As a secondary goal of this paper, I will attempt to respond to some of the worries about cultural imperialism in human rights and cross-cultural humanitarian interventions, specifically in the context of global health justice.